2008
DOI: 10.1158/0008-5472.can-07-5916
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Cancer Therapy in a Mouse Model of Neurofibromatosis-1 Optic Glioma

Abstract: Mouse models of human cancers afford unique opportunities to evaluate novel therapies in preclinical trials. For this purpose, we analyzed three genetically engineered mouse (GEM) models of low-grade glioma resulting from either inactivation of the neurofibromatosis-1 (Nf1) tumor suppressor gene or constitutive activation of KRas in glial cells. Based on tumor proliferation, location, and penetrance, we selected one of these Nf1 GEM models for preclinical drug evaluation. After detection of an optic glioma by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 45 publications
4
103
0
Order By: Relevance
“…Immunoreactivity was visualized with the Vectastain avidin-biotin complex and 3,3′-diaminobenzidine (Vector Laboratories). TUNEL labeling was performed as previously described (44). Representative sections were photographed with a digital camera (Optronics) attached to an inverted microscope (Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoreactivity was visualized with the Vectastain avidin-biotin complex and 3,3′-diaminobenzidine (Vector Laboratories). TUNEL labeling was performed as previously described (44). Representative sections were photographed with a digital camera (Optronics) attached to an inverted microscope (Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical evaluation of the suppressive and preventive efficacy of rapamycin for PJS using Lkb1 þ /À mice has revealed that rapamycin effectively reduced the tumor burden in these animals (Wei et al, 2008(Wei et al, , 2009Robinson et al, 2009;. Also in mouse models for NF1 and PHTS, treatment with rapamycin has been shown to reduce tumor growth (Podsypanina et al, 2001;Hegedus et al, 2008;Squarize et al, 2008). At present, one open-label phase II clinical trial is recruiting PJS patients for suppressive therapy with everolimus to determine if this drug can diminish gastrointestinal polyps (clinicaltrials.…”
Section: Treatment Of Lkb1/ampk/tsc-associated Lesions With Mtorc1 Inmentioning
confidence: 99%
“…In astrocytes, neurofibromin loss leads to mTOR-dependent increases in cell proliferation, which reflect mTOR regulation of Rac1 (Sandsmark et al, 2007) and STAT3 (Banerjee et al, 2010). These differences have profound implications with respect to therapeutic drug design and support the use of rapamycin, an immunosuppressant drug, to specifically inhibit the mTOR pathway in Nf1-deficient gliomas (Hegedus et al, 2008) and Schwann cell malignancies (Johansson et al, 2008), and MEK inhibitors for other NF1-associated tumor types.…”
Section: Susceptible Cell Typementioning
confidence: 99%